Potential benefits of employee portals in public administrations: Implementation and proactive behaviour towards the organization - Héctor Marcos Pérez-Feijoo; Francisco José Martínez-López; Mercedes García-Ordaz (Atlantic Review of Economics, 2015)
The aim of this article is the determination of the advantages achieved through the implementation of an employee portal, both for the government and for the users of the portal. We proposed an adaptation of the Huang, Jin and Yang (2004) model, based on the organizational support theory (Eisenberger et al., 1986). This theory predicts a proactive behaviour of employees wheter they perceive a support of the organization. In this case, the trigger for that perception is the satisfaction derived by the benefits to personnel provided by an employee portal. Through an empirical study, conducted among public school teachers, we have found evidence of the perception of organizational support among public employees when the portal is deployes. However we haven't found a link between that support and a proactive behaviour towards the organization.
Keywords: O32; M52; 330; employee portals; e-government; organizational citizenship behaviour; organizational support theory